Electroacupuncture restores intestinal mucosal barrier in IBS-D rats by modulating mast cell-derived exosomal MiR-149-5p - Hou, Yujun; Luo, Fangli; Wang, Kai; Chen, Ying; Wang, Lu; Li, Yanqiu; Wang, Siqi; Yao, Junpeng; Li, Ying; Zhou, Siyuan (Frontiers in Immunology, 2025)
BackgroundIntestinal barrier dysfunction is a key etiology of diarrhea-predominant irritable bowel syndrome (IBS-D), and our previous work has demonstrated that mast cells play a critical role in this process. Here, we further show that electroacupuncture (EA) restores intestinal mucosal barrier in IBS-D Rats by modulating mast cell-Derived exosomal (MC-EXO) microRNAs (miRNAs).MethodsIBS-D was induced in rats using chronic unpredictable mild stress (CUMS) combined with Senna solution administration, and confirmed through assessments of visceral pain threshold, diarrhea index, percentage of time spent in open arms, hematoxylin and eosin staining was performed to evaluate the pathological features of the colon. Model rats were treated with EA in combination with the mast cell agonist C48/80, CRF-R1 agonist Ucn1, or exosome antagonist GW4869. CRF and CRF-R1 mRNA expression levels were measured using qPCR, and mast cell activation and degranulation were examined by transmission electron microscopy (TEM) and immunohistochemistry (IHC). Additionally, intestinal barrier integrity and tight junction expression were evaluated by ELISA, TEM, Western blot (WB), and IHC. MC-EXO miRNAs were extracted, sequenced, and subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Furthermore, Caco-2 cells were transfected with miR-149-5p and miR-22-5p mimics to determine the effect of these miRNAs on intestinal permeability and tight junction protein expression. To further validate the effect of miR-149-5p, IBS-D rats were administered adeno-associated viruses (AAV) overexpressing miR-149-5p, and mast cell activation and intestinal barrier function were evaluated.ResultsEA alleviated IBS-D symptoms by downregulating CRF and CRF-R1 expression, inhibiting mast cell activation, and upregulating tight junction protein expression. These effects were abrogated by CRF and mast cell agonists, but enhanced by an exosome inhibitor. MiRNA sequencing revealed significantly higher miR-149-5p and miR-22-5p expression levels in the model group compared to the EA group. KEGG and GO enrichment analyses showed that these miRNAs were enriched in pathways associated with tight junctions. Transfection of Caco-2 cells with miR-149-5p or miR-22-5p mimics increased monolayer permeability and downregulated the expression of tight junction proteins. Additionally, administration of AAV-miR-149-5p abolished the protective effect of EA in IBS-D rats.ConclusionMC-EXO miR-149-5p modulates EA-mediated intestinal barrier repair in IBS-D rats.